Pontifex maximus w religii i państwie rzymskim - Kowalski, Henryk (Vox Patrum, 2004)
The function of pontifex maximus belonged to the most important posts in Roman’s religion and State. Roman tradition attributed its establishment to the second king: Numa Pompilius. The name itself, is probably derived from two words: pons and facere. According to modern scientists, at the beginning, he was only a chairman of the college of pontifex, with time this post had more religious and political meaning. Pontifex maximus had great religious prerogatives, however, it was limited, at the beginning, by other priests, officials and senate. The importance of this post grew with its politicization. This fact was used by Caesar to strengthen his power. At the same time, religious competences and accumulation of priest’s functions became one of the signs of its charismatic power that formed basis for future deification. Direction of those changes was perpetuated be Caesar August. Since his times, the function of pontifex maximus as the highest priest, has become one of the foundations (besides imperium maius and tribunicia potestas) of the power of princeps. The fact that it was joined with the membership in all most important priests’ colleges, gave it, in fact, unlimited supervision over all religious matters and, at the same time, it strengthened the political power. The spread of Christianity in the IV century AD didn’t bring any changes at the beginning, emperors still used these titles. The title of pontifex has been gradually used by Popes since emperors: Gracianus and Theodosius.